Collaborative Networking of Researchers in Quality: A Portuguese Case - Pires, A. R. (2018)
Purpose – Experience of a Portuguese network of researchers in quality is presented, and future development is discussed based on literature related to business collaborative network. Design/methodology/approach – Literature review based on company’s networks was used whenever applicable, and it was adapted to individual networks. A critical analysis of the network is carried out, bearing in mind development along its functioning during 9 years. Findings – The experience shows some positive achievements (ex. a scientific journal), and some difficulties (ex: common projects). However, the most important issues for future sustainability are related to management dimensions like structure, strategy, earnings, relationships and performance. Research limitations/implications- Higher Education Institutions are increasingly competing for resources and students. Small Research and Development (R&D) teams, such as quality, face relatively more difficulties than large ones. Collaborative networking can be a good solution. Practical implications- Conclusions and reflection may interest other countries and regions. Social implications- The weak mutual knowledge among quality researchers, as well as the lack of synergies between groups and individuals, can be a seriously weak point for development and scientific production. Coopetition can be possible and advantageous. Originality/value- Research on quality issues is often carried out in small R&D teams. Collaborative networking can improve both theoretical and practical development.